1987
DOI: 10.1111/j.1365-2494.1987.tb02094.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fertilizer nitrogen rate, white clover variety and closeness of cutting on herbage productivity from perennial ryegrass/white clover swards

Abstract: Four varieties of white clover (small‐leaved cv. Aberystwyth S184. medium‐leaved cv. Grasslands Huia and large‐leaved cvs Linda and Olwen) were sown at 3 kg ha‐1 together with 10 kg ha‐1 perennial ryegrass cv. Talbot. Herbage productivity was measured for three harvest years, 1979‐81, over four annual rates of fertilizer N (0,120,240 and 360 kg ha‐1) and two closeness of cutting treatments (80 and 40 mm from ground level). A simulated grazing regime of six cuts per year at 3‐ to 6‐week intervals was used. Prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 20 publications
5
43
1
1
Order By: Relevance
“…Les vaches du lot M-N ont donc adapté la hauteur de pâturage afin de maintenir une ingestion d'herbe suffisante. La diminution de la proportion de trèfle dans des prairies recevant de la fertilisation azotée est couramment décrite dans la littérature [19] et est attribuée à une meilleure utilisation de l'azote minéral par les graminées, avec pour conséquence une plus forte compétition pour la lumière entre graminées et légumineuses [17,25].…”
Section: Caractéristiques Phytotechniquesunclassified
“…Les vaches du lot M-N ont donc adapté la hauteur de pâturage afin de maintenir une ingestion d'herbe suffisante. La diminution de la proportion de trèfle dans des prairies recevant de la fertilisation azotée est couramment décrite dans la littérature [19] et est attribuée à une meilleure utilisation de l'azote minéral par les graminées, avec pour conséquence une plus forte compétition pour la lumière entre graminées et légumineuses [17,25].…”
Section: Caractéristiques Phytotechniquesunclassified
“…The range in these estimates resulted from differences between years and between sites. In Scotland, Frame & Boyd (1987) found that 360 kg N/ha per year resulted in almost complete loss of white clover from mixed pastures within 2-3 years and they concluded that repetitive N fertiliser use was incompatible with white clover persistence and production.…”
Section: Introductionmentioning
confidence: 99%
“…Severalstudiesundermowingandsheepgrazing have shown greater production from large-leaved cloversin swardswithryegrass (Lolium perenne L.) (Widdup &Turner1983;vandenBoschet al 1986;Frame & Boyd 1987). Few studieshave examined thesecloversfordifferences innitrogen(N) fixation and for effects on grass growth and N uptake.…”
mentioning
confidence: 99%